ICT dalam pendidikan: Prospek dan cabaran dalam pembaharuan pedagogi - Robiah Sidin; Nor Sakinah Mohamad (penerbit ukm, 2007)
Because the globalization age revolves around information and communication technology (ICT), educational development should therefore place importance on the socialisation and mastery of ICT skills among students. Changes should be made to the teaching and learning system in the classrooms where the constructivist method is preferred. This approach can promote enthusiasm and encourage students to be more responsible for their learning thus inculcating lifelong learning amongst them. A quasi experiment was conducted to see the effect on students’ achievement of the apprentice approach (constructivist) versus the traditional approach (behavioural) in learning computer as a subject. In the traditional method, a step by step instruction was provided by the teacher while in the apprentice approach the teacher’s role was that of a facilitator to encourage students to solve problems. Students had to develop web page in groups. The research findings show that there is a significant difference in the students’ achievement. Students’ assignments which used the apprentice approach are of better quality in terms of design ,layout arrangement, colour selection, and all the links in the web page are functioning. As such, the researchers suggest that pedagogical changes should be made consistent with the constructivism learning theory. They should also be integrated in the inservice teaching programs. On going and comprehensive research should also be conducted to ascertain the effects of socialization of ICT on youths is effective and lost lasting.